Reproductive Performance of Zi-Goose Promoted by Red Color Illumination - Li, Manyu; Liang, Chen; Zhao, Xiuhua; Liu, Guojun; Zhang, Yuanliang; Yue, Shan; Zhang, Zhiqiang (Frontiers in Veterinary Science, 2022)
Red light can increase the average weekly egg production rate, production and qualified production. It can increase the serum GnRH level and decrease the serum PRL, MT and T4 levels. Red light for 12 h increased the average weekly laying rate, average qualified egg production and hatching rate of seed eggs, and increased the serum levels of FSH, LH, P4, E2, MT, T3 and T4. Blue light at 14 h can improve the average weekly egg production rate, average egg production and average qualified egg production, and reduce serum PRL and MT levels to ensure the improvement of reproductive performance of goose.A total of 705714 overlapping group sequences, 471145 transcript sequences and 268609 single gene sequences were obtained from 18 sequencing samples, with total length of 323.04 M, 668.53 M and 247.88 M, respectively. 176416 unigenes were annotated successfully in 6 databases, accounting for 65.68% of the total Unigene obtained. 2106, 2142 and 8892 Unigene were identified in hypothalamus, pituitary gland and ovary of Goose with different expression of light regulation. Hypothalamus, ovary and pituitary were involved in 279, 327 and 275 KEGG metabolic pathways in light response, respectively. Through further significance analysis and differential discovery rate control, a total of 5 metabolic pathways were obtained which were closely related to reproductive hormones of goose. Ten candidate genes related to reproductive performance of goslings were selected according to the identification results of differentially expressed genes of goslings under red light and white light conditions and genes involved in metabolic pathways significantly related to reproductive hormones of goslings. The expression levels of gnRh-1 in hypothalamus, GNRh-R, FSHβ and LH β in pituitary gland, and FSH-R and LH-R candidate genes in ovary were higher under 12 h red light than white light. However, the expression levels of VIP, PRL and PRL-R candidate genes in hypothalamus, pituitary and ovary were lower under 12 h red light than under 12 h white light.